A Numerical Model for the Analysis of Leading-Edge Protection Tapes for Wind Turbine Blades. (January 2020) - Major, D; Palacios, J; Maughmer, M; Schmitz, S
Abstract: This paper presents results of a numerical study on the effect of a standard leading-edge protection (LEP) tape on the aerodynamics of a NACA 64-618 airfoil. Two numerical models are used in STAR-CCM+ to estimate the impact of LEP tapes on airfoil c l and c d . The objective is to determine which numerical model resolves the physical mechanisms responsible for the aerodynamic degradation observed with standard LEP tapes. Experimental c d data are collected for LEP tapes applied to the tip section of an utility-scale wind turbine blade for numerical validation. For a standard LEP tape, experiments indicate laminar-to-turbulent boundary-layer transition occurs at the LEP tape edge, resulting in a 62% increase in c d . To capture the boundary-layer transition at the LEP step, transition modeling is required in STAR-CCM+. This is an important finding as the mesh techniques developed in this work can be used for future LEP tape design to prevent early transition, thereby reducing the associated adverse impact on wind-turbine tip-section airfoil aerodynamics and annual energy production.